Correlation between physicochemical changes of seeded and seedless watermelons during postharvest storage - Mohd Ali, Maimunah; Hashim, Norhashila; Bejo, Siti Khairunniza; Shamsudin, Rosnah (Inderscience, 2020)
The physicochemical changes in fruits can be influenced by postharvest handling during the storage period. The physicochemical properties (firmness, soluble solids content, pH, moisture content, and colour) were analysed over seven interval days to observe the changes between the seeded and seedless watermelons. The results indicated a decrease in the firmness, soluble solids content, and moisture content values, whereas the pH values increased for both seeded and seedless watermelons. The L*, b*, and chroma values increased whereas the a* value reduced. The hue angle value increased for both seeded and seedless watermelons. Principal component analysis (PCA) was used to determine the quality changes of both varieties and correlations among the physicochemical properties of watermelon samples. The findings indicated that PCA has the potential to characterise quality changes patterns in the seeded and seedless watermelons during storage and could establish the basis of major impact on the determination of fruit quality.